2002
DOI: 10.1089/109264202762252776
|View full text |Cite
|
Sign up to set email alerts
|

The Perspective Effect of Wide-Angle Lenses in Laparoscopes

Abstract: INTRODUCTION IN MINIMALLY INVASIVE SURGERY (MIS), the use of small incisions to provide access and the use of an endoscope for visualization result in some limitations for the surgeon. 1,2 For example, instrument motion is mirrored because the incision acts as a pivoting point. Furthermore, in comparison with natural vision, endoscopic vision is monocular and usually presents the operating area from an unnatural viewpoint. In the literature, these effects are known to disturb the surgeon's spatial perception 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Perspective distortion occurs whenever the angle between the distal face of the endoscope and the plane of the object being viewed is not zero, and it is greater as RA is increased. There have been concerns that the use of angled endoscopes can be less safe and can lead to disorientation; and it has been observed that surgical performance is reduced for just a small contribution from perspective distortion . Perspective distortion is often not fully appreciated, particularly the fact that it can occur as much in the standard 0° endoscope, which is favored in many branches of endoscopic surgery because it is considered to exhibit less field distortion, as it can in any angled endoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perspective distortion occurs whenever the angle between the distal face of the endoscope and the plane of the object being viewed is not zero, and it is greater as RA is increased. There have been concerns that the use of angled endoscopes can be less safe and can lead to disorientation; and it has been observed that surgical performance is reduced for just a small contribution from perspective distortion . Perspective distortion is often not fully appreciated, particularly the fact that it can occur as much in the standard 0° endoscope, which is favored in many branches of endoscopic surgery because it is considered to exhibit less field distortion, as it can in any angled endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…b), which occurs when the optical axis of the endoscope lens is not perpendicular to the surface of the object. Accurate localization, distance perception, and image feature registration are dependent on the endoscopist compensating for these artifacts, either consciously or subconsciously …”
Section: Introductionmentioning
confidence: 95%